Stratigraphy and petroleum posibilities of Los Humocaros-El Tocuyo Region, Lara State, Venezuela - Malandrino, Guiseppe; Escobar, Marcos (Revista Técnica da Faculdade de Engenharia da de Zulia)
Geological Mapping of a 900 km2 area at the Los Humocaros-El Tocuyo region, the State of Lara, Venezuela, leads to the identification of ten outcropping units, together with the anticlinorioum of the eastern flank of the Barbacoas Platform and four main regional faults (from east to west, Hato Viejo, Humocaro, Tocuyo and Boconó faults). The heteropic relationship between the Palaeocene and Eocene formations was established; the precise location of the overthrusting of the allochthonous rocks identified (Barquisimeto Formation) and the location of the main underground strutures over the central-eastern section of the area under study, including the prediction of potential hydrocarbon traps, were determined. The potential source rocks of the Aguardiente, La Luna and Colón formations outcropping on the Los Humocaros-EI Tocuyo sedimentary section was evaluated by means of Rock-Eval pyrolysis. The results indicate overmature source rocks of the units studied. TTI maturity model establishs the beginning of the oil window on Late Palaeocene-Early Eocene age, with the main generation and expulsion at the Late Oligocene-Miocene epoch. As a consequence of a compresive tectonic event which occurred in Late Eocene-Oligo-Miocene, the existence of oil traps with petroleum feeding across great inverse faults was postulated. Recent tectonic episodes reported on the Mio-Pliocene and Quaternary periods, could affect the oil accumulation in terms of their redistribution or their loss by surface migration as oil seeps.